Effective venetoclax-based treatment in relapsed/refractory multiple myeloma patients with translocation t(6;14) - Andrea Ceglédi; Zoltán Csukly; Mónika Fekete; András Kozma; Zsuzsanna Szemlaky; Hajnalka Andrikovics; Gábor Mikala (Frontiers Media S.A., 2023)
Introduction: The selective Bcl-2 inhibitor venetoclax has shown promising therapeutic potential in multiple myeloma, particularly in cases associated with t(11;14) IGH::CCND1 translocation. However, the efficacy of venetoclax in myeloma patients with the t(6;14) IGH::CCND3 translocation remains less investigated.Methods: In this study, we conducted a retrospective analysis to investigate the efficacy of venetoclax-based therapy in relapsed/refractory myeloma patients with t(6;14) translocation. The treatment courses of three patients, that included previous therapies and responses to venetoclax, were assessed. Clinical data, laboratory results, and adverse events were analyzed to evaluate treatment outcomes.Results: Our findings demonstrated remarkable therapeutic responses in three consecutive patients with t(6;14) translocation-associated myeloma who received venetoclax-based therapy. Patient 1, a lenalidomide-bortezomib-daratumumab and alkylator treatment refractory patient, achieved sustained stringent complete remission (sCR) after combining carfilzomib-dexamethasone with venetoclax, which was his best response ever. Similarly, Patient 2, refractory to frontline bortezomib-thalidomide-dexamethasone therapy, attained CR following a transition to bortezomib-dexamethason-venetoclax treatment. Patient 3, who was immunomodulatory (IMID)-intolerant, showed a highly favorable response to venetoclax-dexamethasone therapy after his first relapse following autologous stem cell transplantation. No significant adverse effects were observed in any of the patients.Discussion: Our study provides compelling preliminary evidence for the efficacy of venetoclax in t(6;14) translocation-associated myeloma. The outcomes observed in our patients suggest that venetoclax-based therapy holds substantial promise as an effective treatment option for this specific genetic subgroup. Furthermore, the similarities in treatment response between t(11;14) and t(6;14) translocation subgroups highlight the importance of personalized approaches targeting specific genetic abnormalities to optimize therapeutic outcomes.